Evaluation of controlled hydroxychloroquine releasing performance from calcium-alginate beads - Canan Armutcu; Sena Pişkin (Hittite Journal of Science and Engineering, 2021)
The aim of this study was to develop an effective controlled drug delivery system based on alginate beads for the treatment of autoimmune diseases such as Rheumatoid Arthritis (RA) and Systemic Lupus Erythematosus (SLE). The present study describes the drug delivery systems to control the effective uses of hydroxychloroquine (HCQ) by Ca-alginate beads. The characterization techniques were employed to evaluate the physicochemical properties as scanning electron microscopy (SEM), swelling test (S), hydrolytic degradation (weight loss, WL) and Fourier transform infrared-attenuated total reflection (FTIR-ATR). The release studies from alginate beads prepared in various drug dose were carried out in the aqueous solutions at different pH (5–8) and temperature (4-37oC). The approximately half-amount of HCQ in HCQ-AB3 was released in 12 h and about 84.38% was released within 8 days. Kinetic model, Korsmeyer-Peppas was applied to model the HCQ release kinetic of alginate beads, which corresponded to non-Fickian transport mechanism.